Improving Students’ Reading Comprehension through Communicative Language Teaching(CLT) - Rahmati Rahmati (ITScience (Information Technology and Science), 2021)
The research aims to find out whether the students reading comprehension can be improved through the use of the Communicative Language Teaching(CLT) method. In order to achieve the objectives, the researcher held action research at SMA N 5 Lhokseumawe, from 16- 19th March 2021. There were 2 cycles in which 2 meetings were held for each cycle. The subject of the study is the second year with the numbers of population 32 students. The instruments used were observation sheets, questionnaires, and tests. The result of the study is the problem of motivating students to read. This can be solved by using Communicative Language Teaching(CLT). Based on the questionnaire, all of the students said that the use of the Communicative Language Teaching(CLT) method was interesting. In line with the questionnaire result, the observation sheet also showed excellent results on students’ study habits. There was an improvement in students’ comprehension, it can be seen in cycle 1 which was 89.06 points, and cycle II which was 95.6 points. In this study, I suggest that the teachers should be able to use Communicative Language Teaching(CLT) as an alternative to motivating students learning.